KNOWLEDGE AND TRUTH: A SKEPTICAL CHALLENGE. (25th November 2019) - Buckwalter, Wesley; Turri, John
Abstract: It is widely accepted in epistemology that knowledge is factive, meaning that only truths can be known. We argue that this theory creates a skeptical challenge: because many of our beliefs are only approximately true and therefore false, they do not count as knowledge. We consider several responses to this challenge and propose a new one. We propose easing the truth requirement on knowledge to allow approximately true, practically adequate representations to count as knowledge. In addition to addressing the skeptical challenge, this view also coheres with several previous theoretical proposals in epistemology.